2016
DOI: 10.1037/dev0000118
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sensitivity and effortful control in early childhood as predictors of adolescents’ adjustment: The mediating roles of peer group affiliation and social behaviors.

Abstract: Longitudinal links between early childhood temperament, maternal sensitivity, and adolescents' adjustment have been proposed and found in several longitudinal studies, but the mechanisms of influence have not been explored. The authors examined the paths from maternal sensitivity and temperament in early childhood to adolescents' prosocial, aggressive, and delinquent behaviors via childhood social behaviors and peer group affiliation. Data at 54 months, Grade 3 (M age = 9.03, SD = .31), Grade 6 (M age = 11.95,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 65 publications
5
18
0
1
Order By: Relevance
“…Furthermore, we found that delinquent peer affiliation was positively associated with aggressive behavior. This finding is consistent with previous research showing that peer relations are a risk factor for problem behaviors ( Zhu et al, 2015 ; Laible et al, 2016 ). From a social learning perspective, which can explain this association, adolescents who affiliate with delinquent peer may actively develop aggressive behaviors because of their frequent contact, shared activities, and interpersonal affective connectedness with delinquent peers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, we found that delinquent peer affiliation was positively associated with aggressive behavior. This finding is consistent with previous research showing that peer relations are a risk factor for problem behaviors ( Zhu et al, 2015 ; Laible et al, 2016 ). From a social learning perspective, which can explain this association, adolescents who affiliate with delinquent peer may actively develop aggressive behaviors because of their frequent contact, shared activities, and interpersonal affective connectedness with delinquent peers.…”
Section: Discussionsupporting
confidence: 93%
“…Adolescents who affiliate with delinquent peers gradually urge adolescents who were exposed to peer victimization to develop aggression by repeated peer reinforcement for aggressive behavior and peer pressure to imitate others’ aggressive behavior ( Dishion et al, 1996 ). Indeed, previous research revealed that delinquent peer affiliation mediates the association between ecological risks (e.g., maladaptive parenting, corporal punishment, poor school climate) and aggression ( Laible et al, 2016 ; Wang et al, 2017 ; Zhu et al, 2017 ). For instance, Laible et al (2016) reported that maternal sensitivity and temperament in early childhood could exert an indirect effect on adolescents’ aggressive behaviors via delinquent peer affiliation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the explanatory power of these studies is limited because only when these variables are investigated jointly is it possible to test their additive effects and to determine how much variance each factor explains whereas the other is controlled for. Among the few studies that have examined longitudinally both child dispositional characteristics and environmental variables simultaneously, most investigated the relation of parenting and temperament to the development of prosocial behaviour (Eisenberg, Spinrad, Taylor, & Liew, 2017;Hastings, Rubin, & DeRose, 2005;Laible et al, 2017;Laible, Carlo, Davis, & Karahuta, 2016;Streit, Carlo, Ispa, & Palermo, 2017). Studies concerning empathy (Taylor, Eisenberg, Spinrad, Eggum, & Sulik, 2013) or sympathy (Robinson, Zahn-Waxler, & Emde, 1994;Taylor, Eisenberg, & Spinrad, 2015) are even more rare.…”
Section: Introductionmentioning
confidence: 99%
“…(May & Casazza, 2012), life changes that entail new and different social relationships (peer groups or social settings, independence from the family, etc.) (Laible, Carlo, Davis, & Karahuta, 2016), establishing career (Negru-Subtirica & Pop, 2016), and romantic orientations (Spinrad & Gal, 2018), maintaining a continual physical or aesthetic condition (Fernández-Bustos, González-Martí, Contreras, & Cuevas, 2015), and sometimes practising high-performance competitive sport (Molina, Chorot, Valiente, & Sandín, 2014). Inevitably, everything set out here reveals the vulnerability of the wellbeing and distress process, and so consistent regulation of stress as a learned process involving interaction between the individual and her environment will make it possible to construct facilitating resources for a functional response to it (Breeding and Anshel, 2015;Lizmore, Dunn, & Dunn, 2017).…”
mentioning
confidence: 99%